FORMULATION, CHARACTERIZATION AND IN-VITRO DISSOLUTION STUDY OF GLIMEPIRIDE, Β-CYCLODEXTRINS INCLUSION COMPLEXES AND WATER SOLUBLE POLYMERS TERNARY SYSTEMS (the article is withdrawn) - Y.NAIT BACHIR,; N.OUENNOUGHI,; K.DAOUD, (International Journal of Pharma and Bio Sciences, 2013)
Through the years, β-cyclodextrins (BCDs) have been used in order to increase the solubility of insoluble drugs in water. The aim of the present work was to improve the solubility of glimepiride (GLIM), one of the third generation sulfonylurea used for treatment of type 2 diabetes. Inclusion complexes of glimeperide (GLIM) in β- cyclodextrin (BCD) and hydroxypropyl β-cyclodextrin (HPBCD) were prepared using four different methods: physical mixture, kneading method, Freeze-drying and coevaporating method with stoichiometric molar ratio 1:1; drug content estimation found that co-evaporating is the best one of them. Characterizations of inclusion complexes were carried out by the Fourier transform infrared spectroscopy (FTIR), Simultaneous Thermogravimetry-Differential Scanning Calorimetry (TG-DSC) and X-rays diffraction (XRD), these studies indicated the inclusion of glimeperide in the cavity of BCDs. The ternary systems glimeperide, β-cyclodextrins inclusion complexes and water soluble polymers (PEG 1500, PEG 4000, PEG 6000, PVP K30, PVP K90, HPC, and HPMC) were prepared with the co-evaporating method. In-vitro dissolution study of pure drug and all formulations have been released, the formulation which presents the best dissolution rate was Glimeperide -Hydroxypropyl β-cyclodextrin-PEG 1500 ternary system, the dissolution rate has attended more than 90%.